2015
DOI: 10.1016/j.jcis.2014.12.040
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the interfacial behaviour of dilute light-switching surfactant solutions

Abstract: The direct molecular modelling of an aqueous surfactant system at concentrations below the critical micelle concentration (pre-cmc) conditions is unviable in terms of the presently available computational power. Here, we present an alternative that combines experimental information with tractable simulations to interrogate the surface tension changes with composition and the structural behaviour of surfactants at the water-air interface. The methodology is based on the expression of the surface tension as a fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 51 publications
1
30
0
Order By: Relevance
“…The SAFT force field does not suffer from the aforementioned limitations and has been shown to reproduce in a quantitative manner the behavior of complex fluids and, of particular interest to this case, ethoxylated surfactants and photosensitive surfactants in water. 31 In our study, the surfaces correspond to unstructured walls with an integrated potential that depends only on the energy potential parameters and the distance to the surface. 32 The baseline surface is paraffinic in nature, parametrized so that a pure water droplet has an average contact angle of 60°, corresponding to the conditions for which the optimum superspreading behavior is observed experimentally.…”
Section: ■ Methodologymentioning
confidence: 99%
“…The SAFT force field does not suffer from the aforementioned limitations and has been shown to reproduce in a quantitative manner the behavior of complex fluids and, of particular interest to this case, ethoxylated surfactants and photosensitive surfactants in water. 31 In our study, the surfaces correspond to unstructured walls with an integrated potential that depends only on the energy potential parameters and the distance to the surface. 32 The baseline surface is paraffinic in nature, parametrized so that a pure water droplet has an average contact angle of 60°, corresponding to the conditions for which the optimum superspreading behavior is observed experimentally.…”
Section: ■ Methodologymentioning
confidence: 99%
“…Finally, following the general methodology proposed by Segura et al, 43,44 the molecular parameters of pure fluids can be calculated by forcing the EoS to exactly reproduce the experimental vapor pressure, the local slope of the vapor pressure curve, and the density and compressibility of the liquid phase at one single reference temperature in terms of the theory of displacements. 45,46 In this work we modeled THF as a single-and double-segment pearl-necklace model, without any additional electrostatic interactions, estimated from the corresponding states principle (or critical data) proposed by Mejía et al 41 This methodology has shown great flexibility to characterize vapor-liquid interfacial properties of pure fluids 47 and complex mixtures of dilute surfactant solutions 48 and natural gases and condensates. 47,[49][50][51] Table I summarizes the SAFT parameters for THF as used in molecular simulations in this work.…”
Section: A Saft-coarse Grained Mie Force Fieldmentioning
confidence: 99%
“…The SAFT-γ Mie EoS is used here to inform CG force-field parameters representing the interactions between the chemical groups characteristic of PFAA molecules that can then be used as input in direct molecular simulation. The SAFT-γ Mie methodology has already been applied to develop an efficient parametrization of CG force fields over a broad range of conditions for a variety of molecular fluids, including carbon dioxide [45][46][47], other greenhouse gases and refrigerants [48], aromatic compounds [49], water and aqueous mixtures [50][51][52][53], n-alkanes [48,54], and amphiphilic systems comprising nonionic [55], light-switching [56], and super spreading surfactants [57]. The procedure for the determination of the molecular parameters can be further simplified with a corresponding states treatment [58].…”
Section: Introductionmentioning
confidence: 99%